1999
DOI: 10.1007/bf03168790
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of use and satisfaction with a university-based teleradiology system

Abstract: zona has been operating a teleradiology program for almost 2 years. The goal of this project was to characterize the types of cases reviewed, to assess radiologists" satisfaction with the program, and to examine case turnaround times. On average, about 50 teleradiology cases ate interpreted each month. Computed tomography (CT) cases are the most common type of case, constituting 65% of the total case volume. Average turnaround time (to generate a "wet read" once a case is received) is about 1.3 hours. Image qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Kennedy et al [2] found that teleradiology improved RTAT. A second [128] teleradiology study also reported positive findings. The results of both studies suggest that teleradiology might improve RTAT, however, this must be balanced against other quality parameters such as costs and referring clinicians' satisfaction [164].…”
Section: Productivity-enhancing Technologiesmentioning
confidence: 86%
See 2 more Smart Citations
“…Kennedy et al [2] found that teleradiology improved RTAT. A second [128] teleradiology study also reported positive findings. The results of both studies suggest that teleradiology might improve RTAT, however, this must be balanced against other quality parameters such as costs and referring clinicians' satisfaction [164].…”
Section: Productivity-enhancing Technologiesmentioning
confidence: 86%
“…Two (3.5 % of 57) studies on teleradiology met the inclusion criteria. Both studies found that teleradiology improved RTAT [2,128]. For example, the proportion of reports completed within 40 min increased from 34 (95 % CI 29, 38) to 43 % (95 % CI 39, 47) pre-and postintervention, respectively, p<0.01 [2].…”
Section: Teleradiologymentioning
confidence: 92%
See 1 more Smart Citation
“…The main reason for this is that digitized images generally are of poorer quality which leads to reduced diagnostic confidence. 3,29 When digitizers are used, there is evidence that for the most part digitizers are fairly equivalent in terms of acceptable contrast and low geometric distortion (even the less expensive non-radiology specific ones), thus there are circumstances where these solutions are acceptable. 30 Even with digitally acquired images, however, there is considerable variability in the quality of images between sites, both as a function of the basic imaging procedures and the equipment used, so users need to be aware of these variations and account for them during the interpretation process.…”
Section: Image and Interpretation Qualitymentioning
confidence: 98%
“…The main reason for this is that digitized images generally are of poorer quality which leads to reduced diagnostic confidence. 4,5 When digitizers are used, there is evidence that for the most part digitizers are fairly equivalent in terms of acceptable contrast and low geometric distortion (even the less expensive non-radiology specific ones), thus there are circumstances where these solutions are acceptable. 6 Even with digitally acquired images, however, there is considerable variability in the quality of images between sites, both as a function of the basic imaging procedures and the equipment used, so users need to be aware of these variations and account for them during the interpretation process.…”
Section: Lack Of Specialistsmentioning
confidence: 99%